-4(7x+9)=-2(14x+28)

Simple and best practice solution for -4(7x+9)=-2(14x+28) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(7x+9)=-2(14x+28) equation:



-4(7x+9)=-2(14x+28)
We move all terms to the left:
-4(7x+9)-(-2(14x+28))=0
We multiply parentheses
-28x-(-2(14x+28))-36=0
We calculate terms in parentheses: -(-2(14x+28)), so:
-2(14x+28)
We multiply parentheses
-28x-56
Back to the equation:
-(-28x-56)
We get rid of parentheses
-28x+28x+56-36=0
We add all the numbers together, and all the variables
20!=0
There is no solution for this equation

See similar equations:

| 3/4t=14 | | 7(3n+5)=6(6n+9)+6 | | 3x+9=7x-4x+9 | | ​z+4(2z+3)=15z+4(2z+3)=15 | | 6n+18=14 | | /⅓j=4 | | 2^3+2^5x=45 | | 9=-6x+3(x-5) | | /⅓j=4* | | -5(-7x+7)=-20 | | |8a-4|=20 | | 3x+4–6x=12+5x | | x=-2/3-6 | | -2(x+3)=4x.3. | | 7(1-2y)-3=4-2y | | 7x-13=8x-24=180 | | 11x+1=-8+12x | | -4(x+3)7x-6=24 | | -44-22=9j+2j | | b/10–1=1 | | 6-9=6x-8x-15 | | b−16=20 | | 13m-7-10m=2m | | 2(x-5)=9+3x+6+8+3x | | 7x-13+8x-24=180 | | 10-16=9a-7a | | 1=k/11 | | 4x+16=240 | | 2+2m=14 | | 70x(x+19.1)=(10x+40)(7x+-245.7) | | 5(2x+9)=2(2x-10+8x | | 2/3+6=1/6x+11 |

Equations solver categories